Effect of Red Bean Diet on Blood Glucose Concentration of Alloxan-Induced Diabetic Rats - Y Marsono; Zuheid Noor; Fitri Rahmawati (Jurnal Teknologi dan Industri Pangan, 2003)
Hypoglycemic response of red bean were evaluated in alloxan-induced diabetic rats. The objective of this research was to evaluate the effect of red bean (Vigna umbellata) diet compare with soy bean diet on blood glucose concentration in alloxan-induced diabetic rats. Thirty male Sprague-Dawley (SD) rats (250-300 g) were diabetic induced by alloxan injection (80 mg/kg of body weight by intra muscular injection). They were divided into three groups of ten rats. They were fed (1) Standard diet (STD), (2) Red bean diet (KM), and (3) Soy bean diet (KD) for 28 days. Concentration of serum glucose were determined before injection (0 day),after injection (day 17th) and every sweek during diet intervention (day 24,31,38 and 45th) It was found that alloxan injection increased serum glucose concentration of STD, KM, and KD rats. After 28 days intervention, red bean decreased the serum glucose concentration from 217, 87 mg/dL to 57,70 mg/dL (69 %) in KM groups and from 218,94 mg/dL to 76,82 mg/dL (65 %) in KD groups, but standard diet (STD) were decreased less than both of KM and KD diet. Key words : Diabetic, alloxan-induced, hypoglicemic, red bean, and soy bean